The effect of carbonization on wood structure of dalbergia violacea, stryphnodendron polyphyllum, tapirira guianensis, vochysia tucanorum, and pouteria torta from the Brazilian Cerrado - Gonçalves, Thaís A.P. [UNESP]; Marcati, Carmen R. [UNESP]; Scheel-Ybert, Rita (Brill Academic Publishers, 2012)
Brazil is the world's largest producer of charcoal and a great part of this material still comes from native forests - especially from the cerrado biome, which is highly impacted by anthropogenic degradation.The need to control charcoal production increases the demand of charcoal identification, but there is little information about the anatomical modifications due to carbonization. In this paper, fresh and charred wood samples from five Brazilian species were analyzed (Dalbergia violacea, Stryphnodendron polyphyllum, Tapirira guianensis, Vochysia tucanorum, and Pouteria torta). Anatomical characters were described and measurements of the main anatomical features of wood and charcoal were statistically compared. Minor modifications were observed: reduction of tangential vessel diameter was the most evident change after carbonization; shrinkage of rays (in width) occurred only in some individuals. The present study supports the identification of charred woods, hopefully contributing to the control of charcoal production, and to palaeoenvironmental and archaeobotanical studies.
Keywords: Anthracology; Brazil; Cerrado; Charcoal; Wood anatomy